помогите пожалуйста!))))  ●1 y'''-y'=3x^2-2x+1    ●2 y'''+y''-6y'=(20x+14)e^2  

   помогите пожалуйста!))))  ●1 y'''-y'=3x^2-2x+1    ●2 y'''+y''-6y'=(20x+14)e^2  
Гость
Ответ(ы) на вопрос:
Гость
Ответ: Y^3+Y^2-3*X^2-1=0 Выражение: Y^3+Y^2-6*Y^1=(20*X+14)*e^2 Ответ: Y^3+Y^2-6*Y-20*X*e^2-14*e^2=0 Решаем по действиям: 1. (20*X+14)*e^2=20*X*e^2+14*e^2 2. Y^3+Y^2-6*Y-(20*X*e^2+14*e^2)=Y^3+Y^2-6*Y-20*X*e^2-14*e^2 Решаем по шагам: 1. Y^3+Y^2-6*Y-(20*X*e^2+14*e^2)=0 1.1. (20*X+14)*e^2=20*X*e^2+14*e^2 2. Y^3+Y^2-6*Y-20*X*e^2-14*e^2=0 2.1. Y^3+Y^2-6*Y-(20*X*e^2+14*e^2)=Y^3+Y^2-6*Y-20*X*e^2-14*e^2  Окончательный ответ: Y^3+Y^2-6*Y-147.781121978614*X-103.44678538503=0    
Не нашли ответ?
Ответить на вопрос
Похожие вопросы